Preparing for MQF documentation: A manual - Mohd Yusoff, Nurahimah; Shaari, Ahmad Jelani; Abdul Karim, Hamida Bee; Md Ali, Ruzlan; Veloo, Arsaythamby; Hanafi, Zahyah; Mustafa, Ismail (Universiti Utara Malaysia Press, 2011)
Accreditation is a certification of the academic quality of an institution of higher learning.Some countries require accreditation and others consider it as optional.Some countries accredit through official government agencies while others appoint independent or private organizations that oversee the whole educational accreditation process. In Malaysia, the Malaysian Qualifications Agency (MQA) is the sole responsible body to monitor the accreditation process for all Higher Education Institutions (HEIs).This manual is a standard reference to assist lecturers and teachers in preparing MQF documents.It sets to provide clear guidelines on details of how to prepare all documents necessary for MQA accreditation.The contents of the manual emphasize:Understanding the Malaysian Qualifications Framework,Programme objectives, programme learning outcomes, course objectives and course learning outcomes, Course syllabus, the scheme of work and mappings, Course assessment and preparing the Test Specifications Table Student Learning Time, Preparing the Internal Quality Audit (IQA)